An annotated list of planthoppers with alternate hosts from Kallar tract of Punjab, Pakistan - Rizwan, Muhammad (2020)
Diversity of planthoppers and their host plants were studied in the "Kallar" tract of the Punjab, Pakistan (an important growing area of the world for producing Basmati rice). Planthoppers are considered the most important pests of rice. Delphacidae and Cixiidae are families of planthoppers with the most harmful species. Delphacids are primarily vector of the viruses, whereas Cixiids are vectors of phytoplasmas, mycoplasmas and prokaryotes-like associated to the class Mollicutes. Specimens of planthoppers were collected from the rice fields and surrounding weeds. A list of Fulgoromorpha is provided, with distributional and biological records as well. Records are extracted primarily from field data and specialized reference sources. Seven species from two different families of Fulgoromorpha were related to rice ecosystem (Cixiidae, one species and Delphacidae; six species). Three Delphacid species, whitebacked planthopper Sogatella furcifera, brown planthopper Nilaparvata lugens and small brown planthopper (SBPH) Laodelphax striatellus are well-known vectors of severe rice pathogenic diseases in the Oriental and Paleartic regions. Laodelphax striatellus was recorded on rice for the first time in Pakistan. Among alternate hosts, Trifolium alexandrium, Leptochloa chinensis, Helianrhus allus, Medicago polymorpha and Sorghum bicolor were recorded for L. striatellus, while Leptochloa chinensis, Helianrhus allus, Medicago polymorpha, Sorghum bicolor, Zea mays and Cynodon dactylon were recorded for S. furcifera for the first time. N. lugens was recorded on weeds Leptochloa chinensis and Medicago polymorpha.